Knowledge Valuation by Iranian Women with High-Risk Pregnancy: A Qualitative Content Analysis - Zahra Shojaeian; Talat Khadivzadeh; Ali Sahebi; Hossein Kareshki; Fatemeh Tara (Shiraz University of Medical Sciences, 2020)
Background: Gaining adequate knowledge about high-risk pregnancy (HRP) and correct understanding of the condition, empowers women to improve the use of prenatal care, practice better self-care, and reduce the risk of pregnancy complications. The present study aimed to assess the valuation of knowledge by Iranian women with HRP. Methods: The present qualitative study was conducted on 25 women with HRP from August 2017 to August 2018 at various educational hospitals in Mashhad, Iran. The data were collected through in-depth semi-structured interviews. The data collection process continued until data saturation. The data were analyzed using the conventional content analysis method and MAXQDA software (version10.0). Data collection and data analysis were conducted concurrently. Results: Based on the analysis of the interviews, two main categories and eight sub-categories were extracted. The main categories were "Positive valuation of credible problem-relevant knowledge" and "Avoidance of misleading and stressful information". The results showed that various factors had a positive impact on knowledge gathering, namely personal and other people's experiences, obtaining need-based information, sympathetic advice from others, and faith-based health recommendations. On the other hand, factors that had a negative impact were related to the type of information that caused stress, was unreliable, inefficient or incompatible with personal goals. Conclusion: The findings of the present study would help health care providers to offer suitable and empathetic counseling to women with HRP. Providing valid and accessible sources of information will lead to faster and timely referrals of such patients.